Tetraarylpyrrolo[3,2-b]pyrroles as versatile and responsive fluorescent linkers in metal-organic frameworks - Gunnlaugsson, Thorfinnur; Schmitt, Wolfgang (My University, 2018)
The first examples of crystalline coordination polymers containing the tetraarylpyrrolo[3,2-b]pyrrole (TPP) fluorophore are presented. We have prepared three new TPP ligands L1, H2L2 and H2L3, containing nitrile, carboxylate and mixed imidazole-carboxylate donor functionality, respectively. The ligands themselves each show significant fluorescence in the solution phase, with the nitrile species exhibiting solvatofluorochromism and the two carboxylate-containing compounds exhibiting concentration-dependent emission colour suggesting aggregation processes in solution. Three 3-dimensional polymeric structures are then presented. The compound poly-[AgL12]SbF6·3THF·2H2O 1 is an eightfold-interpenetrated diamondoid material, while poly-[Zn4O(L2)3]·20DMA·10H2O 2 is a porous Metal-Organic Framework with pcu topology, and both 1 and 2 show notable luminescence in the solid state. Complex 2 readily undergoes guest exchange accompanied by a reversible switching in emission colour with no change in chemical structure. While complex poly-[CdL3]·2.5DMA·3.5H2O 3 is non-emissive, it displays a twofold interpenetrated pts topology with hexagonal symmetry and an extremely long hexagonal pitch of 100.3 Å, and shows an impressive 22 wt% CO2 uptake capacity at 278 K and 1 bar.
Keywords: crystalline coordination polymers; TPP ligands L1, H2L2 and H2L3; Metal–Organic Framework